Hygienic Practices and Fungal Contamination: Evaluation of Commercial Tricyclists and Contact Surfaces of Tricycles within Gombe Metropolis - admin, Aliyu S. I.; Adamu M. T.,; Salahudeen A.,; Benedicta, Agbo; Ummu R. A,; Sadisu, Abubakar; Saleh, Fatima (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Tricycles (“Keke napep”) are a popular means of transportation in Gombe especially Gombe Metropolis, Nigeria, particularly for moderate-to-lower income earners. However, concerns exist regarding unknown hygienic practices as fungi frequently contaminate contact surfaces and therefore pose a significant threat to tricycle passengers hence, this study aimed to assess the knowledge, attitudes, and practices (KAP) regarding hygienic practices amongst tricycle users and level of tricycle fungal contamination within Gombe Metropolis. A cross-sectional survey was conducted involving random data collection from 250 tricyclists (collected in duplicate). Descriptive and inferential statistics and standard microbiological techniques were used to analyze the collected data and samples. Antifungal susceptibility testing (AST) was carried out using standard disc antibiotics. The findings revealed that most respondents demonstrated good knowledge of hygienic practices (65.2%), while a significant proportion (74.4%) observed poor hygiene practices in tricycles. Fungi isolates such as Candida albicans and Aspergillus niger were isolated from the study. A. niger and C. albicans exhibited sensitivity to fluconazole and ketoconazole but resistant to griseofulvin. These findings underscore the importance of maintaining good hygienic practices to mitigate the risk of disease contraction in tricycles, thus promoting public health and preventing the spread of diseases.